The csnD/csnE Signalosome Genes Are Involved in the Aspergillus nidulans DNA Damage Response - Lima, Joel Fernandes (Copyright © 2005 by the Genetics Society of America, 2005)
The signalosome (CSN) is a conserved multiprotein complex involved in regulation of eukaryotic development and is also required to activate ribonucleotide reductase for DNA synthesis. In Aspergillus nidulans, csnD/csnE are key regulators of sexual development. Here, we investigated whether the csnD/csnE genes are involved in the DNA damage response in this fungus. The growth of the csnD/csnE deletion mutants was reduced by subinhibitory concentrations of hydroxyurea, camptothecin, 4-nitroquinoline oxide, and methyl methanesulfonate. A. nidulans increases csnD/csnE mRNA levels when it is challenged by different DNA-damaging agents. There is no significant transcriptional induction of the csnE promoter fused with lacZ gene in the presence of DNA-damaging agents, suggesting that increased mRNA accumulation is due to increased mRNA stability. Septation was not inhibited in the csnD/csnE deletion mutants while ΔuvsB ΔcsnE presented an increase in septation upon DNA damage caused by methyl methanesulfonate, suggesting that uvsB(ATR) and csnE genetically interact during checkpoint-dependent inhibition of septum formation. The double ΔcsnD/ΔcsnE ΔnpkA mutants were more sensitive to DNA-damaging agents than were the respective single mutants. Our results suggest that csnD/csnE genes are involved in the DNA damage response and that NpkA and UvsB(ATR) genetically interact with the signalosome.